How does better quality data affect the value of a mining project? - Gursuren, Ishjantsan; Maybee, Bryan; Zagdsuren, Ganbaatar (Geological Issues, 2023)
With the advent of 3D software applications into geology and resource modeling world, data quality is going to become an issue. Electronic data can easily be corrupted due to weak data housing and ownership. Many people are aware of the issue, but they may not know how much it can affect the value of a mining project especially when making investment decisions.This research investigates the question How does better quality data affect the value of a mining project? Two geological primary data datasets were created. The first dataset was named “initial”; after manual entry errors were removed a second dataset was named “improved” (or verified). All the data errors raise from inadvertent human mistakes and coming out the source files. The methodology consisted of constructing two models for resource estimation based on both datasets, followed by developing two financial assessments and comparing their results. The approach was applied to evaluate the central orebody of the Erdenet-Ovoo copper-molybdenum group deposits in Mongolia. The actual operational and costing information of the existing operation was used for financial assessment. The most assumptions and parameters for the financial assessment were analysed and estimated to plug into the financial models. The answer to the research question is not just a matter of finding a simple discrepancy in the resource amounts and Net Present Value (NPV) by discounted cash flow models. The study also examines project risks and compares the probabilistic distributions of NPVs for the two models based on the decision-making ability of them. It is found that the improved model is more accurate than the initial one and can provide a better decision making. Specifically, having better-quality data increases the probability of the project to make a profit by over 7% and 2.7% with a higher chance that the NPV will be greater than $100M in this case study.